2018
DOI: 10.1200/edbk_200689
|View full text |Cite
|
Sign up to set email alerts
|

Latest Advances in the Diagnosis and Treatment of Large Granular Lymphocytic Leukemia

Abstract: Large granular lymphocyte (LGL) leukemia has been recognized in the World Health Organization classifications among mature T cell and natural killer cell neoplasms and is divided into three categories. Chronic T cell leukemia and natural killer cell lymphocytosis can be considered as a similar spectrum of an indolent disease characterized by cytopenias and autoimmune conditions. The last category, aggressive natural killer cell LGL leukemia is very rare, related to Epstein-Barr virus, and seen mainly in young … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
97
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(104 citation statements)
references
References 62 publications
2
97
0
Order By: Relevance
“…However, during the disease course in 60% of cases therapy is needed, mostly for cytopenia-related manifestations, symptomatic patients showing clinical features often related to neutropenia (2). Currently, no specific treatment is available for LGL disorders and the current therapy is based on immunosuppressive drugs (i.e., Methotrexate, Cyclophosphamide or Cyclosporine A) giving unsatisfying responses (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…However, during the disease course in 60% of cases therapy is needed, mostly for cytopenia-related manifestations, symptomatic patients showing clinical features often related to neutropenia (2). Currently, no specific treatment is available for LGL disorders and the current therapy is based on immunosuppressive drugs (i.e., Methotrexate, Cyclophosphamide or Cyclosporine A) giving unsatisfying responses (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…There have been many reported cases of T-LGL leukemia associated with underlying autoimmune disorders, malignancy, bone marrow failure, solid organ transplantation, or use of certain drugs. [2][3][4][5][6]13 In general, it is reported to be an indolent type of leukemia and the…”
Section: Discussionmentioning
confidence: 99%
“…[12,22] For T-LGLL, the current diagnostic requirements have lowered this threshold to > 0.4 or 0.5 × 10 9 /L provided that a clonal T-LGL population is found with an appropriate clinical context. [23][24][25] Recent studies have shown that 49% of patients with T-LGLL have no absolute lymphocytosis and 36% of patients have blood LGLs < 1 × 10 9 /L. [9] As the clinical manifestations of RAassociated T-LGLL are often identical to those in which one would suspect an FS, it may be di cult to differentiate RA-associated T-LGLL with a low LGL count (0.4-2.0 × 10 9 /L) from FS.…”
Section: Discussionmentioning
confidence: 99%